“Suiting Up” to Enhance Empathy Toward Aging: A Randomized Controlled Study - Lee, Shaun Wen Huey; Teh, Pei-Lee (Frontiers in Public Health, 2020)
Background: Healthcare professionals who have a positive attitude and who are more empathetic towards older adults are in a better position to deliver quality healthcare. This study examines the impact of using an aging simulation suit on undergraduate pharmacy students’ empathy levels. Methods: One-hundred and twenty first year students enrolled in the Bachelor of Pharmacy course were randomized, to either a medication review polypharmacy workshop (control) or an immersive aging simulation suit and medication review polypharmacy workshop (intervention). Intervention participants donned the aging suit and performed a series of tasks, including walking up a flight of stairs and filling up a form to simulate the physical limitations experienced by an older adult. The workshop was delivered at week 10 of semester. Both groups also completed a medication review polypharmacy workshop at week 12 of semester. The primary outcome was a measurement of change on the Jefferson Empathy Scale – Healthcare Professional Questionnaire among both groups at week 12 of semester. Secondary outcomes include the longitudinal impact of intervention after 3 months of the workshop and perceptions on learning. Results: The use of a simulation suit did not increase participants’ self-rated empathy compared to control. However, the suit enhanced the ability of participants to understand the physical limitations and visual issues associated with aging. Participants felt that it enhanced their health advocacy, as it taught them the importance of listening, patience and respect for older adults. Conclusion: The use of an immersive aging suit can be a useful adjunctive tool to help enhance students’ understanding of the physical limitations and visual limitations of aging. Further research is needed to understand how these limitations affects other healthcare students. Trial registration: ClinicalTrials.gov identifier: NCT04133727